Online community system information system / Chang Choon Tuck - Chang, Choon Tuck (2002)
With the tremendous growth of the Internet and the expansion of the Internet and the expansion of the World Wide Web, more and more facility and information is being put on the Internet. The Internet creates a global communication that break the barrier of time, place and distance within which conducts Online Community System. Online Community System is a system that allows world wide people to create their own community through the Internet for their propose like communicate to each other or sharing an information. This thesis describe the Online Community Information System that allows Internet users sharing information, news and ideas at anywhere at anytime through the Internet. The online community information System has seven modules. Structure diagram is used to shows an overall subsystem or the project. Besides, this project will review the method, technologies and development tools (like waterfall model with prototyping, using Active Server Page on Windows 2000 platform, the web server with back-end database - Microsoft SQL server 7.0) that are used to set up Online Community Information System. At the end this project will implement the entire requirement into a real system and analysis the strengths and weakness of the system. It is hope that the major problems faced by current system can be solved through this project.